Morbidity and Volumetric Progression in Juvenile Nasopharyngeal Angiofibroma in a Long-Term Follow-Up - Epprecht, Lorenz; Mosimann, Marc; Vital, Domenic; Holzmann, David (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective We compare the open and transnasal approaches for the excision of juvenile nasopharyngeal angiofibromas regarding the rate of morbidity, and residual tumor and its symptomatic recurrence over time. In addition, we present volumetric measurements of juvenile nasopharyngeal angiofibromas over time.Methods All surgically treated patients of our institution were reviewed back to 1969 for type of surgery, residual tumor by magnetic resonance imaging (MRI)-based volumetry, recurrence, and morbidity. We performed a prospective clinical and radiological follow-up on reachable patients.Results In total, 40 patients were retrievable from our records. We were able to follow up on 13 patients after a mean of 15.7 years since surgery (range: 1–47 years). Patients operated by the open approach had a higher rate of postoperative complications and thus a higher morbidity than endoscopic patients (4/4 vs 3/9; p = 0.007), although tumor sizes were equal among groups (p = 0.12). Persisting tumor was noted in 3/4 and 4/9 (p = 0.56) patients, respectively. The corresponding mean volumes of residual tumors were 16.2 ± 14.4 cm3 and 10.8 ± 6.6 cm3 (p = 0.27). No progression could be noted in endoscopically treated patients (p = 0.24, mean time between scans 2 years).Conclusions Our analysis shows that the endoscopic approach results in less morbidity. The open approach does not guarantee freedom from persisting tumor tissue. Age seems to be a most important risk factor for the conversion of an asymptomatic persistence into a symptomatic recurrence.
Keywords: angiofibroma; follow-up; morbidity; endoscopic surgery; infratemporal approach